The sword in the stone [videorecording (Blu-ray + DVD)] - Peet, Bill; Bruns, George; White, T. H. (Terence Hanbury), 1906-1964 (Disney Blu-ray., 2013)
The English king dies leaving no heir. In the churchyard of a cathedral in London, a sword appears imbedded in a stone. It is inscribed with a prophecy. Although many try, no one can budge the sword from the stone. Deep in the dark woods, Merlin the Magician begins to teach 11-year-old Arthur, who lives in the castle of Sir Ector where he's an apprentice squire to Sir Kay. Arthur learns the basic truths of life, but he also runs into the evil Madam Mim, who tries to destroy him. A great tournament is held in London to pick a new king. Arthur, attending as Kay's squire, forgets Kay's sword, and runs back to the inn to get it, but the inn is locked. Arthur, seeing the sword in the stone, innocently, and easily, pulls it out. When the knights marvel at the wondrous sword and question where he got it, Arthur has to prove himself all over again by pulling the sword from the stone.